Nutritional Impact of Storage Containers on Macronutrient Integrity of Breastmilk - Marney C. Johnson; Lauryn A. Winter; Diana G. Anzueto Guerra; Rachel Jacob; Donald C. McCurnin; Cynthia L. Blanco (Journal of Breastfeeding Biology, 2019)
This study compared the effect of container material type on macronutrient changes in human breast milk (HBM) during frozen storage. HBM was collected from breastfeeding mothers and baseline macronutrients were analyzed and recorded. The HBM was aliquoted into milk storage containers of five commonly used materials (low-density polyethylene (LDPE), polypropylene (PP), glass, stainless steel, and silicone). The samples were frozen in a standard freezer (-20°F) for 30, 60, and 180 days prior to thawing and retesting macronutrient values. In the 155 samples analyzed, macronutrient changes among different types of storage materials were insignificant at 30 and 60 days of frozen storage. When comparing macronutrients at baseline to 180 days, there was a significant decrease in protein value over time in LDPE containers as compared to silicone containers (p=0.001). Likewise, there was a significant decrease in total calories from baseline to 180 days in both PP and LDPE containers compared to silicone (p=0.046 and 0.013, respectively). While not significant for short-term storage, HBM has losses of macronutrients (protein) with long-term storage in LDPE and PP plastics. These differences could have major nutritional impact on growth, particularly to infants born prematurely.
Keywords: macronutrient